O sono na adolescência: Como o professor, o aluno e sua família lidam com ele? - Lima, Maria de Lourdes Alves de (2006)
This research aimed to analyze how secondary teachers deal with the sleepiness of their adolescents students, when it occurs in classroom. In order to do so, the review of the literature focused on authors who studied sleepiness at school and, also, those who adopted, in studying human development, either a social-historical theoretical framework or an inatista one: Wallon, Vygotski and Gesell. The first two authors believed, as the researcher do, that man is, at birth, only a candidate to humanity, needing to become human through interactions with its social and physics environment. The method employed interviews (during the morning period) with two teachers of a public school situated at east side of São Paulo, one of their students and her mother. Observations of the dynamic of the classroom and of the way teachers deal with pupil s sleepiness were also done. The results showed that there is permissiveness in treating this aspect and, also, that the teachers did not articulate school environment and the learning that takes place in it. The conclusions pointed out that it is necessary to discuss sleepiness at classroom, either during the time reserved for teachers collective work or during initial teachers formation, since sleep/vigil rhythm, without being noticed, interferes in students learning, during classes